APPLICATION OF MECHATRONIC MODULAR IN THE TRAVERTINE PRODUCTION PROCESS - Oybek Kholmatov; Ibragimov Rakhmatullokhuja (European Science Publishing, 2024)
This paper explores the transformative potential of mechatronic modular systems in travertine production. Travertine, a precious natural stone with a variety of architectural applications, faces challenges in traditional mining and processing methods. The integration of mechatronic modular systems offers innovative solutions to increase efficiency, accuracy and stability throughout the production chain [1]. Mechatronic modular systems revolutionize key aspects of travertine production, from quarry automation to precision cutting, shaping and surface finishing. Their versatility and flexibility facilitate seamless integration, enabling innovation and flexibility in production lines [2]. In addition, the adoption of these systems enhances sustainability efforts by optimizing resource use and reducing environmental impact. Through case studies and analysis, this paper highlights the transformative impact of mechatronic modular systems on the travertine industry and their role in shaping its future competitiveness and success [3].
Keywords: Travertine, mechatronic modular systems, manufacturing process, automation, precision, stability, quarrying, cutting and shaping, surface finishing, integration, flexibility, innovation, efficiency, resource optimization, environmental impact.